129k views
11 votes
-4x-2y=-10
3x+y=4
Using substitution

User OWolf
by
5.3k points

1 Answer

10 votes

Let get x from the first equation

-4x=+2y-10

x=-1/2y + 5/2

Now substitute the x in the second equation

3(-1/2y+5/2)+y=4

-3/2y + 15/2 + y =4

Move the terms without the y to the other side

-3/2y + y = -15/2 +4

Now multiple both side by 2

-3y +2y = -15+8

-y = -7

Y = 7 (ANSWER)

Now we substitute the y in the first equation so we can get the x

x = -1/2 (7) + 5/2

x = -7/2 + 5/2

x = -2/2

X = -1 (SECOND ANSWER)

User Nick Lange
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.